The Role of Hedonic and Utilitarian Value Moderation in the Relationship Between Advertising Value and Purchase Intention: A Study of iPhone and Samsung Smartphone Consumers - Rendy Setiawan; Radityo Putro Handrito (LP2M IAIN Palopo, 2026)
The development of digital technology and the increasing use of premium smartphones such as the iPhone and Samsung indicate that this phenomenon is occurring among various groups in Indonesia. However, the high prices of these products are relatively significant compared to the average income of the population. This phenomenon suggests that consumers' purchasing decisions are not solely influenced by rational considerations but also by psychological factors and value perceptions formed through the products themselves. This study aims to analyze the influence of advertising value on purchase intention among iPhone and Samsung smartphone consumers, as well as to examine the role of hedonic and utilitarian values as moderating variables in this relationship. The research employs a quantitative approach with an explanatory research design. The population consists of consumers and prospective consumers of iPhone and Samsung smartphones in two cities in East Java, namely Surabaya, Malang, Kediri, Madiun, and Blitar. The sampling technique uses purposive sampling with a total of 250 respondents. Advertising value is measured using indicators of valuable, useful, and important, while purchase intention is measured through indicators of probability, consideration, willingness to buy, and performance purchase. Hedonic and utilitarian values serve as moderating variables to determine the extent to which consumers' psychological orientations can strengthen or weaken the influence of advertising value on purchase intention. This research is expected to contribute theoretically to the development of consumer behavior literature and advertising effectiveness, as well as provide practical implications for companies in designing marketing strategies that are more aligned with consumer characteristics.